2018
DOI: 10.3389/fevo.2018.00151
|View full text |Cite
|
Sign up to set email alerts
|

Historical DNA Metabarcoding of the Prey and Microbiome of Trematomid Fishes Using Museum Samples

Abstract: Antarctic specimens collected during various research expeditions are preserved in natural history collections around the world potentially offering a cornucopia of morphological and molecular data. Historical samples of marine species are, however, often preserved in formaldehyde which may render them useless for genetic analysis. We sampled stomachs and hindguts from 225 Trematomus specimens from the Natural History Museum London. These samples were initially collected between 20 and 100 years ago and fixed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
23
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(25 citation statements)
references
References 86 publications
1
23
1
Order By: Relevance
“…More importantly, very few studies have investigated whether host tissue preserved in ethanol, the most common preservative used for museum collections, could be used to investigate long‐term variations in microbiomes of non‐human hosts. The most extensive study on this topic, conducted using trematomid fish tissue collected between 1901 and 2006, showed that only ~10% of samples selected could be successfully used for microbiome analyses (Heindler et al, 2018). However, the authors suggest that many of those samples were probably first stored in formalin before transferring to ethanol (a common practice for museum samples in the past), which may explain the low yield, as formalin is known to cause multiple structural changes in DNA (Heindler et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…More importantly, very few studies have investigated whether host tissue preserved in ethanol, the most common preservative used for museum collections, could be used to investigate long‐term variations in microbiomes of non‐human hosts. The most extensive study on this topic, conducted using trematomid fish tissue collected between 1901 and 2006, showed that only ~10% of samples selected could be successfully used for microbiome analyses (Heindler et al, 2018). However, the authors suggest that many of those samples were probably first stored in formalin before transferring to ethanol (a common practice for museum samples in the past), which may explain the low yield, as formalin is known to cause multiple structural changes in DNA (Heindler et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…The most extensive study on this topic, conducted using trematomid fish tissue collected between 1901 and 2006, showed that only ~10% of samples selected could be successfully used for microbiome analyses (Heindler et al, 2018). However, the authors suggest that many of those samples were probably first stored in formalin before transferring to ethanol (a common practice for museum samples in the past), which may explain the low yield, as formalin is known to cause multiple structural changes in DNA (Heindler et al, 2018). Overall, while there is some indication that samples preserved using a variety of methods may be useful for analysing long‐term trends in host microbiomes, such analyses need to consider the potential for preservational biases.…”
Section: Introductionmentioning
confidence: 99%
“…The advent of genomic sequencing technologies, for example, demonstrated that many historical samples can be valuable to large scale phylogenomic and phylogeographic works (Holmes et al, 2016). Even given the large increase in museum specimen use for genomic sequencing, limited work has focused on characterizing the microbial communities associated with these archived host specimens (Heindler et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…To date, a single study has examined gastrointestinal microbiomes of museum archives (Heindler et al, 2018) using DNA metabarcoding to identify the prey and microbiomes of trematomid fishes. They found limited overlap in microbiome composition between contemporary and museum samples of three Trematomus species archived in either formaldehyde or ethanol; however, they hypothesized that differences could reflect actual biological shifts in the gut microbiome of these fishes.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation